NILAI KELESTARIAN ALAM DAN HUBUNGAN SPIRITUAL DALAM CERPEN “AMA TEWO” KARYA SILVESTER PETARA HURIT - Sirilus Karolus Keroponama Keban; Yohana Hingi Tefa (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2025)
This study aims to describe the values of nature conservation and spiritual relationships in the short story "Ama Tewo" by Silvester Petara Hurit. This study uses a literary ecology approach in analyzing the values of nature conservation and spiritual relationships reflected in the narrative about the importance of land, forests, and natural resources as an inseparable part of the identity and survival of society. Spiritual relationships are depicted in beliefs in ancestral spirits, traditional rituals, and the belief that humans must live in harmony with nature. The results of the study can be concluded that there are values of nature conservation and spiritual relationships in the short story "Ama Tewo" by Silvester Petara Hurit, including (1) the value of maintaining integrity, (2) the value of sacrifice, (3) cultural values, and (4) the value of preserving created nature.